The Role of ChatGPT AI in Student Learning Experience - Anggia Viorennita; Laksmi Dewi; Cepi Riyana (Universitas Pendidikan Indonesia (UPI), 2023)
Artificial Intelligence (AI) has received significant attention in the educational context, and one of the prominent forms of AI is ChatGPT (Generative Pre-trained Transformer). This study aims to conduct a literature review on the role of ChatGPT AI in student learning experiences. This literature review research focuses on the use of ChatGPT in supporting the learning process of students at various levels of education. The literature review method is used to collect, evaluate, and synthesize the latest literature that is relevant to the research topic. The results of the literature review show that the use of ChatGPT AI in education has grown rapidly in recent years. ChatGPT has been applied in a variety of educational contexts, including as a learning assistant, virtual tutor, assignment corrector, and interactive learning aid. Some of the benefits of using ChatGPT AI in education include increasing the accessibility of learning materials, providing fast and personalized feedback, and encouraging student engagement and learning motivation. However, some challenges need to be addressed, such as ethical concerns, data privacy concerns, and technology limitations. This study concludes that AI ChatGPT has great potential to change the way students learn by providing adaptive and personal assistance in the learning process. To support more effective learning experiences, practitioners and decision-makers in the education sector need to understand the potential and limitations of using ChatGPT.